2014
DOI: 10.1093/toxsci/kfu268
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Toxicity, in vivo and in vitro, Associated with Inhibition of Nicotinamide Phosphoribosyltransferase

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) is a pleiotropic protein with intra- and extra-cellular functions as an enzyme, cytokine, growth factor, and hormone. NAMPT is of interest for oncology, because it catalyzes the rate-limiting step in the salvage pathway to generate nicotinamide adenine dinucleotide (NAD), which is considered a universal energy- and signal-carrying molecule involved in cellular energy metabolism and many homeostatic functions. This manuscript describes NAMPT inhibitor-induced retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 24 publications
2
59
1
Order By: Relevance
“…In these clinical studies, thrombocytopenia was demonstrated to be the dose-limiting toxicity (30,33). Retinopathy, degeneration and loss of the photoreceptor and outer nuclear layers of the retina, was reportedly associated with FK866/APO866 and CHS 828/GMX-1778 in the rat (30,34). Similar toxicity findings were also reported for other NAMPT inhibitors (35,36).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…In these clinical studies, thrombocytopenia was demonstrated to be the dose-limiting toxicity (30,33). Retinopathy, degeneration and loss of the photoreceptor and outer nuclear layers of the retina, was reportedly associated with FK866/APO866 and CHS 828/GMX-1778 in the rat (30,34). Similar toxicity findings were also reported for other NAMPT inhibitors (35,36).…”
Section: Introductionsupporting
confidence: 62%
“…First, this molecule only causes retinopathy in the dog, but not in the rat as compared with other NAMPT inhibitors (30,34,35). Second, the retinal toxicity associated with the molecule could be rescued with NA coadministration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of the NAMPT-E2F2-ID pathway to these specific molecular contexts is an interesting question for future investigation. It should be noted, however, that inhibiting NAMPT carries therapeutic challenges, because systemic NAMPT inhibition is known to cause retinal toxicity and potential blindness (30). Therefore, local NAMPT inhibitory strategies or disruption of the tumor-specific signals regulating NAMPT or its downstream consequences need to be carefully considered for potential clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that NAMPT inhibition leads to a reduction in NAD + intracellular levels, which can induce apoptosis in cancer cells 2a, 3. However, it has also been reported that targeting of NAMPT might lead to side effects such as blindness 4. A strategy called PhotoActivated ChemoTherapy (PACT) might solve selectivity issues 5.…”
mentioning
confidence: 99%